The Methodology of the Source Base of Historical and Pedagogical Research - Elena Adamenko (Pedagogical Discourse, 2013)
The methodology of the formation of the research base of historical and pedagogical research which is the definition of its structure and necessary amount of sources was grounded. It is defined that, as a rule, the structure of the source base of such study consists of: 1) the sources that allow you to develop a research methodology; 2) the sources which are the theoretical basis of the study, and 3) the authentic sources (primary sources). It is proved that the main methodological requirement for the composition and quantity of primary sources is an opportunity to reach them with the help of the optimal number of the most significant facts about the subject of the study. The possibilities of application of the sampling method for the formation of the source base of historical and pedagogical research are shown.